Analysing, modelling and promoting tangible and intangible values of building heritage with historic flame lighting system. - Lassandro, P.; Fioriello, C.S.; Lepore, M.; Zonno, M. (Journal of Cultural Heritage, 2021)
• New multidisciplinary methodology for historical flame-based lighting system reconstruction in order to promote the fruition of architectonic heritage. • 3D digital models for lighting analysis through combined surveys by laser scanner and photogrammetric techniques with historical hypotheses. • Experimental campaign to measure the physical features of different olive and lentisk oil lamps. • The virtual reality and ICT for the enhancement of the historical heritage, integrating scientific data with historical studies and documentation on artificial lighting by flame. • Methodology validation on a middle-age rock church and a Roman villa. The aim of this research is to define a multidisciplinary method capable of enhancing the tangible and intangible values of the historical-cultural heritage through the virtual reconstruction of the ancient internal flame lighting systems. The survey by laser scanner and/or by digital photogrammetry and solid modelling were the techniques used to carry out the three-dimensional reconstructions of the artefacts. The 3D model based on archaeological and historical documentation made it possible to define the lighting scenarios according to various historical-interpretative hypotheses and the reconstruction of the used luminaires. Instead, the laboratory experiments on the flame allowed obtaining the scientific reference parameters to be used in the virtual reconstruction of the lighting scenarios. This method was validated in two different case studies. The first is a cave church in Matera, a medieval religious building built entirely in the ravine with evident architectural signs that enabled to identify the ancient lighting systems. The second is a Roman villa in Mola di Bari, a devastated archaeological site among which several Roman lamps were found, thanks to which it was possible to start the study of light. In addition to making an important contribution to the community of scholars, the lighting scenarios obtained from the research also aim to enhance the architectural artefacts and promote the related history knowledge for future generations. Virtual reality, augmented reality and online 3d visualization can be some of the possible applications towards which this research can converge to promote the fruition of cultural heritage.